Religion in international relations theory interactions and possibilities - Sandal, Nukhet A.; Fox, Jonathan 1968- (Routledge studies in religion and politics, 2013)
There is a growing realization among international relations scholars and practitioners that religion is a critical factor in global politics. The Iranian Revolution, the September 11 attacks, the ethno-religious conflicts such as the ones in the former Yugoslavia and Sri Lanka are among the many reasons for this increased focus on religion in international affairs. The rise of religious political parties across the world ranging from the Christian Democrats in Europe to Bharatiya Janata Party in India similarly illustrated religion's heightened international profile. Despite all this attention, it is challenging to situate religion within a discipline which has been dominantly secular from its inception. Only a few existent works have ventured to integrate religion into core international relations theories such as Classical Realism, Neorealism, Neoliberalism, Constructivism and the English school. This work is the first systematic attempt to comparatively assess the place of religion in the aforementioned theoretical strands of international relations with contemporary examples from around the world. Written in an accessible and systematic fashion, this book will be an important addition to the fields of both religion and international relations.